Hypomagnesaemia among Diabetic Patients with Chronic Kidney Disease: A Cross-sectional Study - Mahiyuddin, Najeeb; Khan, Nazia Nusrat; Jannat, Miftahul; Mizan, Md Saif Bin; Rahim, Muhammad Abdur; Uddin, Khwaja Nazim (Bangladesh Critical Care Journal, 2024)
Background: The clinical role of magnesium, especially of hypomagnesaemia, in diabetic and chronic kidney disease patients has been underestimated for many years. Objective: To determine the frequency of hypomagnesaemia in diabetic patients with chronic kidney disease and to investigate the relationship of magnesium level with glycemic and renal status. Methodology: This was a cross-sectional observational study performed on 100 diabetic patients with chronic kidney disease, admitted to BIRDEM General Hospital, Dhaka, Bangladesh, excluding patients with history of chronic diarrhea, laxative abuse, diuretic use, alcoholism and those on dialysis. Several socio-demographic and biochemical parameters were analyzed and compared with magnesium level. Results: Frequency of hypomagnesaemia among the study population was 37% (p= 0.009) and the frequency was found to be increasing with increasing stage of chronic kidney disease. Frequency of hypomagnesaemia was more in patients with uncontrolled fasting blood glucose, post meal blood glucose and HbA1c level (p<0.05). Serum magnesium levels positively correlated with serum creatinine levels (Pearson’s correlation coefficient, r=0.428, p=0.001) and inversely correlated with GFR (Pearson’s correlation coefficient, r= -0.275, p= 0.006). Conclusion: The frequency of hypomagnesaemia among diabetic patients with chronic kidney disease is common. So it would be prudent to routinely monitor for hypomagnesaemia in diabetic patients with chronic kidney. Bangladesh Crit Care J September 2024; 12 (2): 132-137